2023
DOI: 10.3390/rs15092292
|View full text |Cite
|
Sign up to set email alerts
|

MF-DCMANet: A Multi-Feature Dual-Stage Cross Manifold Attention Network for PolSAR Target Recognition

Abstract: The distinctive polarization information of polarimetric SAR (PolSAR) has been widely applied to terrain classification but is rarely used for PolSAR target recognition. The target recognition strategies built upon multi-feature have gained favor among researchers due to their ability to provide diverse classification information. The paper introduces a robust multi-feature cross-fusion approach, i.e., a multi-feature dual-stage cross manifold attention network, namely, MF-DCMANet, which essentially relies on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…As AI advances, a paradigm shift from conventional feature extraction techniques to DL algorithms, particularly CNNs, has emerged. Utilizing CNNs for feature extraction has led to heightened efficiency and accuracy in detecting targets within IoT systems ( Li et al, 2023a ). Notably, Li et al (2023a) and Li et al (2023b) demonstrated that a multi-scale analysis modulation recognition network employing denoising encoders, deep adaptive threshold learning, and multi-scale feature fusion significantly improved recognition accuracy in low signal-to-noise ratio environments.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As AI advances, a paradigm shift from conventional feature extraction techniques to DL algorithms, particularly CNNs, has emerged. Utilizing CNNs for feature extraction has led to heightened efficiency and accuracy in detecting targets within IoT systems ( Li et al, 2023a ). Notably, Li et al (2023a) and Li et al (2023b) demonstrated that a multi-scale analysis modulation recognition network employing denoising encoders, deep adaptive threshold learning, and multi-scale feature fusion significantly improved recognition accuracy in low signal-to-noise ratio environments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Utilizing CNNs for feature extraction has led to heightened efficiency and accuracy in detecting targets within IoT systems ( Li et al, 2023a ). Notably, Li et al (2023a) and Li et al (2023b) demonstrated that a multi-scale analysis modulation recognition network employing denoising encoders, deep adaptive threshold learning, and multi-scale feature fusion significantly improved recognition accuracy in low signal-to-noise ratio environments. Meanwhile, the network shows the adaptive learning ability of different noise thresholds and the advantages of effective feature fusion modules under various modulation types ( Li et al, 2023b ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the synthetic aperture principle and making use of the Doppler information generated by the relative motion of the radar platform and the target being detected, spaceborne synthetic aperture radar (SAR) is a high-resolution microwave imaging technology [1][2][3][4]. It has a variety of characteristics, such as all-time, all-weather, high-resolution large width, and has a certain degree of surface penetration, offering it a unique advantage in applications such as disaster monitoring, marine monitoring, resource surveying, mapping and military [5][6][7][8][9]. Recent publications provide an overview of the application of satellite remote sensing technology to natural hazards such as earthquakes, volcanoes, floods, land-slides, and coastal flooding [10][11][12].…”
Section: Introductionmentioning
confidence: 99%